(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
Malnutrition happens when the body lacks enough essential nutrients. Children are more vulnerable than adults and face greater risks of serious health problems from poor nutrition. This study examined nutritional assessment for children living with HIV/AIDS. A descriptive cross-sectional study was conducted among 180 respondents at three HAART-providing hospitals in Abia State, namely Abia State University Teaching Hospital (ABSUTH), Seventh-day Adventist Hospital, and Living World Hospital. The study revealed that most caregivers were aged 30–34 years, with a mean age of 33.7 years, and nearly half of the children were between 5 and 9 years old. While over 80% of caregivers knew the classes of food, only about half identified proper child nutrition, and many were unaware of the link between HIV and malnutrition. Exclusive breastfeeding was practiced by 55%. Children’s diets were predominantly carbohydrate-based due to low income. About 38% had recent diarrhea, and 66% were on ART. Anthropometric results showed most children within normal growth percentiles, likely reflecting ART adherence and moderate caregiver nutrition knowledge. The study concluded that although caregivers showed moderate awareness of nutrition, socioeconomic challenges and limited understanding of the relationship between HIV and malnutrition affect dietary diversity and child health outcomes. Based on the findings, it is recommended that continuous nutrition education be provided for caregivers of HIV-positive children, focusing on balanced diets and the nutritional impact of HIV. Government and NGOs should also support income-generating programs and provide nutritional supplements to improve dietary quality and child well-being.